EFFICACY AND SAFETY OF SUPINE PERCUTANEOUS NEPHROLITHOTOMY IN OBESE PATIENTS - Bhatti, Kamran Hassan; sohail, Nadeem; Gomha, Faaz; Shaat, Ahmed; Mohammad Abdel Rahman , Khalid; Albodour, Amjad; Mohammed Smain, Ayman; Saad Alhabash, Salvan; Mohammad Ali, Hassan; Ahmed Channa, Aftab (Journal of Ayub Medical College Abbottabad, 2024)
Background: Obesity is an increasing health concern, affecting 39% of the population. In Qatar, in recent years, the obese population contributed 35.9% of men and 46.1% of women. Qatar's obesity prevalence is higher in the region. The diet, rich in animal protein, high in oxalate, low in calcium, and the dry subtropical desert climate are risk factors for urolithiasis in Qatar. Objectives were the efficacy of percutaneous nephrolithotomy in obese patients. Patients and Methods: We retrospectively reviewed the patients who underwent PCNL between January 2015 and December 2019. A total of 150 patients were enrolled. The patients were categorized into two groups according to BMI: <30 kg/m2 (group 1, non-obese) and >30 kg/m2 (group 2, obese). The stone clearance rate, operation time, duration of hospital stays, Postoperative analgesic use, and postoperative complications were compared among groups. The chi-square test was used to analyze variables and Complications were graded according to the Clavien-Dindo classification system. Results: The BMI values of 110 patients were lower than 30 kg/m2, while 40 patients' BMI values were higher than 30 kg/m2. There was no significant difference between operation time, fluoroscopy time, number of access points, or access sites when the two groups were compared. No significant difference was found in the total length of hospital stay, haemoglobin drop, or complication rates. Immediate stone-free rates were 81.8% in the non-obese group and 75% in the obese group (p=0.21). Conclusion: In a retrospective study of 150 patients undergoing supine PCNL, the efficacy was not different between non-obese and obese patients. This is the first study evaluating these outcomes for PCNL performed under the ERAS protocol in the supine position. Further multicenter and prospective studies are required to verify these findings.